2015
DOI: 10.1002/ccd.26301
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of atherothrombotic burden before stent deployment in non‐ST elevation acute coronary syndromes: Reduction of myocardial necrosis achieved with nose‐dive manual thrombus aspiration (REMNANT) trial. A volumetric intravascular ultrasound study

Abstract: Manual TA reduces atherothrombotic burden in culprit lesions of NSTE-ACS patients before S-PCI and, when deep plaque removal is obtained, TA optimizes subsequent stent expansion. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…24) However, clinical studies regarding thrombus aspiration in NSTEMI could not show clinical benefits, 27,28) while thrombus aspiration might decrease atherothrombotic burden. 29) Therefore, there have been no established strategies to reduce slow flow in PCI to the culprit lesion of NSTEMI.…”
Section: Discussionmentioning
confidence: 99%
“…24) However, clinical studies regarding thrombus aspiration in NSTEMI could not show clinical benefits, 27,28) while thrombus aspiration might decrease atherothrombotic burden. 29) Therefore, there have been no established strategies to reduce slow flow in PCI to the culprit lesion of NSTEMI.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke was defined as a major ischemic or hemorrhagic cerebrovascular accident resulting in disabling neurological symptoms for at least 24 hr. Repeat target‐vessel revascularization was defined as recurrent ischemic symptoms that resulted in the need for revascularization by either PCI or coronary bypass surgery …”
Section: Methodsmentioning
confidence: 99%
“…In total 45 patients with no reflow or slow flow after PCI received intracoronary bolus of glycoprotein IIb/IIIa inhibitors (tirofiban, 10 μg/kg) with a subsequent intravenous infusion (0.15 μg/kg per minute) for 12–24 hr. After the procedure, patients routinely received dual anti‐platelet therapy with aspirin 100 mg and a P2Y12 inhibitor (either clopidogrel 75 mg daily, or ticagrelor 90 twice a day) for 12 months after the primary PCI, and 100 mg aspirin daily was prescribed indefinitely …”
Section: Methodsmentioning
confidence: 99%
“…The investigators used IVUS to quantify the percentage increase in lumen volume following thrombus aspiration and showed that aggressive intervention was likely to result in successful stent deployment. 104 Conversely, MRI and PET/CT have been used to determine a lack of clinical efficacy. The dal-PLAQUE study did not show a reduction in vessel wall inflammation using the CTEP inhibitor, dalcetrapib: an agent that is now known to be clinically ineffective.…”
Section: Clinical Translationmentioning
confidence: 99%